2012
DOI: 10.1371/journal.pone.0034953
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Is Prevalent in an Isolated Cave Microbiome

Abstract: Antibiotic resistance is a global challenge that impacts all pharmaceutically used antibiotics. The origin of the genes associated with this resistance is of significant importance to our understanding of the evolution and dissemination of antibiotic resistance in pathogens. A growing body of evidence implicates environmental organisms as reservoirs of these resistance genes; however, the role of anthropogenic use of antibiotics in the emergence of these genes is controversial. We report a screen of a sample o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
387
2
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 577 publications
(437 citation statements)
references
References 46 publications
12
387
2
12
Order By: Relevance
“…But, at the same time, a growing body of evidence points to the potentially important role of environmental microorganisms from ecosystems in which the presence of antibiotics produced by humans is expected to be very low or completely absent. Such ecosystems are as varied as soil [2], a microcave isolated for over four million years [3], and pristine waters [4].…”
Section: Introductionmentioning
confidence: 99%
“…But, at the same time, a growing body of evidence points to the potentially important role of environmental microorganisms from ecosystems in which the presence of antibiotics produced by humans is expected to be very low or completely absent. Such ecosystems are as varied as soil [2], a microcave isolated for over four million years [3], and pristine waters [4].…”
Section: Introductionmentioning
confidence: 99%
“…natural products | metabolite discovery | multivariate statistical analysis I ncreasing evidence is accumulating that a large fraction of antibiotic resistance may be elicited via horizontal transfer of resistance elements from the reservoir of microbial diversity found in soil (1,2). Additionally, bacterial resistance toward a significant subset of antibiotics is rapidly generated vertically by mutations in central housekeeping genes encoding polymerases and ribosomal subunits.…”
mentioning
confidence: 99%
“…Moreover, the VanA protein, one the most important products of glycopeptide resistance genes, has preserved its function and 3D structure over centuries [99]. In another study, bacteria found in caves that had had no contact with the surface for over 4 million years proved to be resistant to 14 different antibiotics [100]. Genotyping and biochemical assays show that resistance genes are present in the microbial pangenome regardless of the human-induced selective pressure [100].…”
Section: обзор эволюция инфекцийmentioning
confidence: 99%
“…In another study, bacteria found in caves that had had no contact with the surface for over 4 million years proved to be resistant to 14 different antibiotics [100]. Genotyping and biochemical assays show that resistance genes are present in the microbial pangenome regardless of the human-induced selective pressure [100].…”
Section: обзор эволюция инфекцийmentioning
confidence: 99%